Performance enhancement of high data rate real-time wireless transmission system using superposition coding and unequal error protection - Al-Hasan, Yaseen Hasan Tahir (2011)
Supporting high system capacity and transmission reliability are among the most challenging issues of the next generation wireless communication systems. The fast growing demand for wireless services coupled with the limitations and high cost of wireless spectrum, further magnify these challenges. In an attempt to solve these challenges, researchers developed various broadband wireless access (BWA) schemes that can share the available bandwidth to transmit multiple signals simultaneously. Despite the marked successes by some of these schemes, the need for further improvements remains high. With this in mind, this thesis proposes novel design frameworks to maximize channel efficiency and enhance the performance of real-time visual data transmission with overloaded Code Division Multiple Access (CDMA) systems. The first part of this thesis proposes new adaptive real-time visual transmission schemes to maximize the transmission reliability, increase data rate, and improve the error performance. It also addresses issues to combat detection ambiguity problem among the visual data layers by employing superposition coding, unequal error protection (UEP) and special diversity techniques. A new Adaptive Modulation and Coding (AMC) techniques have been proposed by which the system adapts its Modulation and Coding Scheme (MCS) to better match the instantaneous channel quality in order to attain high transmission reliability and maximize obtainable data rate. In the second part of this thesis, a novel design of overloaded CDMA framework is proposed to increase the user capacity (number of users which can be accommodated synchronously) and data rate of the direct sequence CDMA (DS-CDMA) systems. In addition to maximizing the user capacity, the proposed scheme combats the detection ambiguity problem among the user signals and improves the error performance of overloaded CDMA multiuser systems by combining the superposition coding and UEP technique within the DS-CDMA. This technique is referred to as superposition coding CDMA (SPC-CDMA). Multiple access interference (MAI) issues in the multiuser CDMA system are also investigated. The proposed SPC-CDMA scheme does not only addresses the near-far problem of the multiuser system but also exploits this phenomenon to further improve the performance of multiuser DS-CDMA system. The proposed schemes for both the real-time visual data transmission and the overloaded CDMA system are then simulated over both the AWGN and fading channels using MATLAB 7.4. Based on the simulation results, the proposed schemes provide 12 dB SNR gain, up to 46% data rate increment, and at least twofold increment in channel capacity or data rate compared to the existing schemes as well provide high transmission reliability by mitigate the MAI among the different transmitted signals without requiring extra recourses.